KINERJA PENDAPATAN DAN BELANJA DAERAH KABUPATEN TULUNGAGUNG SEBELUM, SAAT, DAN PASCA PANDEMI COVID-19 (TAHUN 2017-2022) - Natalia Mega Selvi; Mega Tunjung Hapsari (Universitas Dian Nuswantoro, 2023)
The purpose of this study was to determine the performance of regional income and expenditure in Kab. Tulungagung before, during and after the Covid-19 pandemic in 2017-2022. This study uses the analysis variables of the degree of decentralization, the ratio of financial independence, the ratio of expenditure growth, operational expenditure, capital expenditure, and the ratio of direct and indirect expenditure. The results of this study indicate that the analysis of the decentralization of Kab. Tulungagung 2017-2022 is sufficient, the average financial independence ratio is low with a consultative relationship pattern, the average operational expenditure and capital expenditure are good because operational expenditure is less than 90% and capital expenditure is more than 5%, the ratio of direct indirect expenditure not good because the biggest contribution is in direct spending.